Pengembangan Sistem Kelas Digital SMP Joannes Bosco Yogyakarta - Istiningsih Istiningsih (Jurnal Pengabdian Mitra Masyarakat (JPMM), 2020)
Bantul is a district that can be said to advance in the world of education in the Yogyakarta region, this is evidenced by the existence of a number of favorite schools because of the facilities and achievements obtained by these schools. Of the several schools that are favorite students, there are some schools that are currently less popular because the teaching system that is still conventional has not fully adopted the current technological developments. Joannes Bosco Yogyakarta Junior High School is one of the many schools in the district of Yogyakarta that has not fully utilized technological developments so that the quality of teaching and learning activities has not been able to meet the needs of students who are currently familiar with the world of technology